Test system for the service hybrid of the 2S module for the CMS Phase-2 Outer Tracker upgrade. (1st March 2022) - Dziwok, C.; Feld, L.; Karpinski, W.; Klein, K.; Lipinski, M.; Louis, D.; Oezen, I.; Pauls, A.; Pooth, O.; Repic, M.; Wlochal, M.; ,
Abstract: Alongside the High Luminosity LHC upgrade, the silicon tracker of the CMS detector will be replaced within the scope of the so-called Phase-2 upgrade. The new tracker will consist of an inner part (Inner Tracker with pixelated modules) and at larger radii the Outer Tracker with two different module types (PS and 2S modules). One hybrid type used on these modules is the 2S service hybrid. It provides the optical link connection of a 2S module via the Low Power Giga Bit Transceiver (lpGBT) and a Versatile Transceiver Plus module (VTRx+). It is also responsible for the module power distribution. The different responsibilities of the hybrid require a complete testing, which is performed by a dedicated custom made test card. After a hybrid has been installed on the test card, all signal connections can be tested and verified. The test system is designed to handle a high throughput during mass production. The requirements and the design for the 2S service hybrid test card are presented together with testing results of the first final 2S service hybrid prototypes.